2002
DOI: 10.1159/000064238
|View full text |Cite
|
Sign up to set email alerts
|

A Health Economic Analysis of Autologous Transfusion

Abstract: Background: Autologous transfusion reduces the risk of bloodborne viral infections and may decrease the risk of postoperative infections related to immunomodulation. Previous analyses have shown autologous transfusion to be expensive. Methods: A previously published cost-utility analysis was updated. A Markov cohort simulation model compared autologous blood transfusion to allogeneic transfusion in a hypothetical cohort of patients undergoing elective total hip replacement with respect to discounted quality-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 59 publications
(63 reference statements)
2
31
1
Order By: Relevance
“…Previous work has highlighted the value of preoperative education as a way of helping patients to prepare emotionally and practically for colorectal surgery. 100 In other surgeries, inconsistencies between preoperative education and inpatient experiences in colorectal and colonic surgeries have also been previously identified and our findings accord with these. 25,101 Patients undergoing colorectal surgery expressed enthusiasm about working towards their own recovery, 100 a finding reflected in our work.…”
Section: Overview Of Findingssupporting
confidence: 88%
“…Previous work has highlighted the value of preoperative education as a way of helping patients to prepare emotionally and practically for colorectal surgery. 100 In other surgeries, inconsistencies between preoperative education and inpatient experiences in colorectal and colonic surgeries have also been previously identified and our findings accord with these. 25,101 Patients undergoing colorectal surgery expressed enthusiasm about working towards their own recovery, 100 a finding reflected in our work.…”
Section: Overview Of Findingssupporting
confidence: 88%
“…it was more effective and saved costs, when a certain assumption was made. This assumption referred to the immunosuppressive effect of allogeneic transfusion and implied that, by avoiding this effect, PABD would lead to a reduction in postoperative bacterial infections 9,12,14,15 . For instance, in the analysis by Sonnenberg et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were identified, [6][7][8][9][10][11][12][13][14][15][16] most of which were conducted in the USA. The majority of these studies adopted the societal perspective, although only direct costs were estimated (Table 1).…”
Section: Preoperative Autologous Blood Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the previous analysis may be found in [5]. A more detailed description of our updated model may be found in [6].…”
Section: Overview and Assumptionsmentioning
confidence: 99%